A novel programed frameshift expresses the POL3 gene of retrotransposon Ty3 of yeast: Frameshifting without tRNA slippage - Farabaugh, Philip J. (Cell, 1993)
Most retroviruses and retrotransposons express their pol gene as a translational fusion to the upstream gag gene, often involving translational frameshifting. We describe here an unusual translational frameshift event occurring between the GAG3 and POL3 genes of the retrotransposon Ty3 of yeast. A +1 frameshift occurs within the sequence GCG AGU U (shown as codons of GAG3), encoding alanine-valine (GCG A GUU). Unlike other programed translational frameshifts described, this event does not require tRNA slippage between cognate or near-cognate codons in the mRNA. Two features distal to the GCG codon stimulate frameshifting. The low availability of the tRNA specific for the “hungry” serine codon, AGU, induces a translational pause required for frameshifting. A sequence of 12 nt distal to the AGU codon (termed the Ty3. “context”) also stimulates the event.